2022
DOI: 10.21093/di.v22i2.5046
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Secondary School Students’ Biodiversity Literacy Level

Abstract: The quality of life sustained by human beings is largely possible thanks to the opportunities offered by the biodiversity resources in nature. It is widely accepted that the continuation of this lifestyle largely depends on the sustainable use of consumed and destroyed natural resources. Therefore, teaching biodiversity becomes an important element of science teaching. In this context, it is important to reveal the biodiversity literacy levels of the new generation. This study aims to investigate secondary sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…However, among these, it is seen that there are almost no theoretical and practical studies on teacher training. It is seen that there are very few studies on political literacy in Turkiye, and the existing ones are mostly done by social studies educators (Aslan, 2019;Demir, 2019;Faiz & Dönmez, 2016;Görmez, 2018;İnan, 2016;İnan & Tarhan, 2018;Kara & Tangülü, 2017;Kuş, 2013;Şan, 2019;Şan & Gölgesiz Gedikler, 2020;Tarhan, 2019). In 2018, "political literacy" was included as a skill for the first time in the Social Studies Curriculum (Ministry of National Education [MEB], 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, among these, it is seen that there are almost no theoretical and practical studies on teacher training. It is seen that there are very few studies on political literacy in Turkiye, and the existing ones are mostly done by social studies educators (Aslan, 2019;Demir, 2019;Faiz & Dönmez, 2016;Görmez, 2018;İnan, 2016;İnan & Tarhan, 2018;Kara & Tangülü, 2017;Kuş, 2013;Şan, 2019;Şan & Gölgesiz Gedikler, 2020;Tarhan, 2019). In 2018, "political literacy" was included as a skill for the first time in the Social Studies Curriculum (Ministry of National Education [MEB], 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Demir (2019) suggested that current political issues should be discussed and frequently included in the social studies teaching undergraduate program in order for social studies teacher candidates to become politically literate. When the related studies are examined, it is seen that they are generally aimed at determining the political literacy status and levels of teachers/pre-service teachers and getting opinions (see Akhan, 2013;Aslan (2019); Çınar (2019); Dağ & Koçer, 2019;Faiz & Dönmez, 2016;Görmez, 2018;İnan, 2016;İnan, 2019;İnan & Tarhan, 2018;Kara & Tangülü, 2017;Kuş, 2013;Kuş & Tarhan, 2016;Şan, 2019;Şan & Gölgesiz Gedikler, 2020;Tarhan, 2015;Tarhan, 2019). In addition, when the relevant national literature is examined, it is seen that the political literacy levels of social studies teacher candidates and teachers are not very good, and observed social studies teachers do not include current political issues in the classrooms (see Akhan, 2013;Faiz & Dönmez, 2016;Kuş & Tarhan, 2016).…”
Section: Introductionmentioning
confidence: 99%